THE IMPACT OF GENETIC OPERATORS IN SOLVING MULTIPLE PROTEIN SEQUENCE ALIGNMENT - MANISH KUMAR, (International Journal of Pharma and Bio Sciences, 2015)
Protein multiple sequence alignment is a fundamental task in bioinformatics. Its importance is due to its application in the estimation of the phylogeny tree, prediction of the secondary and tertiary protein structure. Obtaining the best solution in multiple alignment (MSA) is an NP-hard problem. This research work presents a novel and efficient approach for MSA of protein sequences by improving the genetic operators of Genetic Algorithm. We asses our algorithm on different protein benchmarks, e.g., BALIBASE, Swiss Prot and we have compared the obtained results to those obtained with other alignment algorithms, e.g., CLUSTALW, using the Column Score (CS) and Fitness Score. Experimental results show that the proposed one is indeed a better algorithm that can increase solution quality, reduce running time and can increase numbers of match column.